Clarifying the roles of grain boundary and grain orientation on the corrosion and discharge processes of α-Mg based Mg-Li alloys for primary Mg-air batteries. (30th January 2021) - Yang, Huabao; Wu, Liang; Jiang, Bin; Liu, Wenjun; Song, Jiangfeng; Huang, Guangsheng; Zhang, Dingfei; Pan, Fusheng
Highlights: The macro and micro grain boundaries morphologies of α-Mg based Mg-Li alloys after corrosion and discharge are observed. The correlation between microstructure and anode performance is defined. The discharge properties of LAZ131 and LAZ531 alloys are measured. The LAZ531 alloy possesses high and steady discharge voltage at small discharge current density for long time. Abstract: The corrosion behavior at open circuit potential (OCP) and discharge properties under applied anodic currents of two α-Mg based Mg-Li alloys, i.e., LAZ131 and LAZ531, with different microstructural features for primary Mg-air batteries are investigated. The results show that the grain boundaries contribute equally to the corrosion and discharge processes, which are attacked preferentially than the grain interiors and accelerate the dissolution processes of α-Mg based Mg-Li alloys. The (10−10)/(11–20) orientated grains are attacked preferentially than the (0002) orientated grains on the corrosion and discharge process. The increased corrosion rate and improved discharge properties are attributed to the refinement of grain size, decreased content of (0002) orientated grains and increased content of (10−10)/(11–20) orientated grains. Of those, the LAZ531 alloy possesses high and steady discharge voltage at small discharge current density for long time, with the values of 1.4801 V at 2.5 mA cm −2 and 1.3742 V at 10 mA cm −2 .